GAMBARAN CURAH HUJAN TERHADAP KASUS COVID-19 DI SULAWESI TENGGARA - Andi Muhammad Fadhillah Arfyansah; La Ode Muhamad Sety; Lymbran Tina (Endemis Journal, 2021)
Covid-19 is an inflammatory disease of the lungs that is similar to Pneumonia disease caused by SARS-CoV-2, a type of corona-virus. Rainfall can affect changes in temperature to become cold which makes SARS-CoV-2 more spread out optimally. This study purpose to determine the description of rainfall on the Covid-19 case in Southeast Sulawesi 2020. The research used is quantitative research with a descriptive approach. The population in this study were all monthly Covid-19 cases (March, April, May, June, July, and August 2020) that were recorded at the Southeast Provincial Health Office. The sample in this study were the entire population (Total Sample) of monthly Covid-19 cases recorded at the Southeast Sulawesi Provincial Health Office and rainfall recorded at the Konawe Selatan Climatology Station in March-August 2020. The results of this study indicate that, rainfall tends to affect Covid-19 cases in Southeast Sulawesi, this can be seen in March the rainfall was 231.1 mm / month with 3 cases of Covid-19, April the rainfall increased from the previous month of 252.9 mm / month with the addition of cases Covid-19 of 59 cases, in May the rainfall increased by 354.1 mm / month with 182 cases, in June the rainfall decreased by 299.9 mm / month with Covid-19 cases of 199 cases, in July the rainfall decreased with Covid-19 cases of 419 cases, and in August the rainfall decreased by 53.7 mm / month with Covid-19 of 419 cases. This illustrates that in March-June rainfall tends to affect the addition of confirmed Covid-19 cases and in July-August tends to be influenced by Population Mobility and the lack of application of health protocols (wearing masks and maintaining distance) in the people of Southeast Sulawesi.